Pengembangan Media Papan Sosial Emosional (Pansos) untuk Meningkatkan Perkembangan Sosial Emosional Anak Usia 5-6 Tahun - Fitriyati, Lilia; Juherna, Erna (STKIP Muhammadiyah Kuningan, 2024)
Lilia Fitriyati (NIM: 214223046), Development of Social-emotional Board Media (Pansos) to Improve Social Emotional of 5-6 Years Old Children (PGPAUD), 2023.Early childhood is a golden age, a time when growth and development begin and are on going. One aspect of child development that needs to be developed by educators is the aspect of social development. Social development aspects can be developed with game media. Educators should use interesting media in their learning. One way to develop social-emotional aspects is with Social-emotional Board Media (Pansos).Adopting from the monopoly game This study aims to determine the social-emotional development of children before and after using Social-emotional Board Media (Pansos) for children aged 5-6 years at Kober Nur Ismail. The purpose of this research and development is to find out the increase in children's social-emotional abilities through the use of learning media Social-emotional Board (Pansos). This type of research is research and development by adopting Sugiyono's steps. The research method used in this research is Research and Development (R&D) using steps from Borg and Gall which are simplified into stages, namely potential and problems, data collection, product design, design validation, design revision, product testing. The subjects of this study were children at Kober Nur Ismail who were 5-6 years old. From the results of the study it was known that there was an increase in social emotional development by 42.5% with the results of the initial presentation during the pre-test 40% and post-test 82.5%